Development of heat storing poly(acrylonitrile) nanofibers by coaxial electrospinning - Noyan, Ezgi C. B.; Önder Karaoğlu, Emel; SARIER, NİHAL; ARAT, REFİK (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2018)
New thermal energy storage materials were developed as poly(acrylonitrile) (PAN) nanofibers with encapsulated phase change materials (PCMs). Sixteen samples composed of PAN shells and PEG or PEGME cores, and one control sample composed of only a PAN shell, were manufactured by coaxial electrospinning. SEM images revealed the formation of randomly distributed, distinct nanofibers with smooth surfaces and cylindrical shapes along their lengths. FTIR results confirmed bicomponent nanofiber structures and TGA results demonstrated their thermal stabilities. Phase change performances of nanofibers were repeatedly examined by DSC analyzes; heating enthalpies ranged from 38 to 133 J g(-1) and from 29 to 60 J g(-1) for PAN-PEGs and PAN-PEGME samples, respectively, corresponding to good encapsulation efficiencies. These remarkable thermal energy storages were achieved at different melting temperatures (- 1 to 60 degrees C). Textile based sandwich structures containing three different types of PAN-PCM nanowebs demonstrated enhanced thermal properties and buffering function against temperature changes in surrounding.
Keywords: Energy materials; Nanocomposites; Thermal properties; Electrospinning; Phase-Change Materials; Thermal-Energy Storage; Glycol/Cellulose Acetate Composite; Differential Scanning Calorimetry; Change Fibers; Mechanical-Properties; Polyurethane Foams; Ultrafine Fibers; Polyacrylonitrile